Essential roles of CTCF binding sites at TAD boundaries in modulating chromatin interactions and transcriptional regulation at the Ifng locus - Muto, Kazuya; Yoshida, Daiki; Suzuki, Toshiyuki; Yamamoto, Natsuo; Inoue, Naokazu; Murakami-Sekimata, Akiko; Iseki, Ken; Sekimata, Masayuki (Frontiers in Immunology, 2025)
Interferon-γ (IFN-γ) is a key cytokine essential for host defense and tumor surveillance, and its expression in T cells is tightly regulated by long-range enhancer–promoter interactions within the Ifng locus. These interactions are organized within topologically associating domains (TADs) and subdomains (intra-TADs), whose boundaries are defined by the architectural protein CTCF. However, the specific contribution of these boundaries to Ifng regulation and chromatin architecture remains incompletely understood. Here, we investigated how chromatin looping within the TAD affects Ifng expression by using chromosome conformation capture (3C) and RNA sequencing in CRISPR-Cas9 genome editing in mice. Deletion of a single CTCF binding site (CBS) at the TAD boundary markedly impaired Th1-mediated immune responses against Cryptococcus neoformans infection and B16 melanoma. This deletion disrupted enhancer–promoter contacts and diminished enhancer-driven activation of Ifng. In contrast, deletion of a CBS within an intra-TAD boundary had no detectable impact on Ifng transcription. Collectively, these findings highlight the essential role of boundary-associated CBS elements in shaping chromatin architecture that enables enhancer–promoter communication and proper transcriptional regulation of the Ifng locus.